Risks associated with introduction of poeciliids for control of mosquito larvae: first record of the non‐native Gambusia holbrooki in Argentina. Issue 2 (10th July 2017) - Cabrera, M. B.; Bogan, S.; Posadas, P.; Somoza, G. M.; Montoya‐Burgos, J. I.; Cardoso, Y. P.
Abstract : This study confirms the presence of two species of the non‐native mosquitofish Gambusia in Argentina. The risks that they represent to native biota, their potential dispersal in the region, and their effectiveness in mosquito larvae control are discussed.